2014
DOI: 10.1123/jsep.2013-0173
|View full text |Cite
|
Sign up to set email alerts
|

Habits Predict Physical Activity on Days When Intentions Are Weak

Abstract: Physical activity is regulated by controlled processes, such as intentions, and automatic processes, such as habits. Intentions relate to physical activity more strongly for people with weak habits than for people with strong habits, but people's intentions vary day by day. Physical activity may be regulated by habits unless daily physical activity intentions are strong. University students (N = 128) self-reported their physical activity habit strength and subsequently self-reported daily physical activity int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 67 publications
1
40
4
Order By: Relevance
“…In order to conceptualise the patterns of effects of explicit and implicit measures on behavior, several dual-process or dual-systems models have been proposed [28,29]. It is important to measure implicit and explicit measures together in order to fully investigate the patterns of effects between the two measures in predicting behaviour [30][31][32][33]. Both the implicit and explicit measures may act synergistically or antagonistically to predict behaviour [31].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…In order to conceptualise the patterns of effects of explicit and implicit measures on behavior, several dual-process or dual-systems models have been proposed [28,29]. It is important to measure implicit and explicit measures together in order to fully investigate the patterns of effects between the two measures in predicting behaviour [30][31][32][33]. Both the implicit and explicit measures may act synergistically or antagonistically to predict behaviour [31].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Although the cross‐sectional design precludes the ability to determine direction of causality, one possible interpretation of these data is that temporal consistency in PA could be beneficial for forming PA habits and fostering a high level of PA. For example, individuals who routinely perform PA at the same time of day may develop stronger cue‐behavior relationships and greater PA automaticity than individuals with a temporally variable PA routine . Consequently, temporally consistent exercisers may be less vulnerable to day‐to‐day fluctuations in deliberate intentions for PA and achieve higher PA levels . Alternatively, it is also possible that individuals who engage in a regular, high level of MVPA happen to develop temporal consistency in their exercise routine over time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, through consistently exercising immediately after work, leaving work may become paired with going to the gym. Strong cue‐behavior associations increase the habitual nature and automaticity (i.e., performance with lowered conscious awareness or volition) of PA, thus reducing the day‐to‐day attention, effort, and motivation required to perform PA .…”
Section: Introductionmentioning
confidence: 99%
“…Neal, Wood & Drolet, 2013). Rebar, Elavsky, Maher, Doerksen, and Conroy (2014) found that individuals with strong exercise habits were likely to exercise even on days when their intention to do so was low(er). Habits are resistant to changes in reflective factors, such as behavioural intentions or beliefs, do not tax cognitive and self-regulatory resources, and are the default behaviour.…”
Section: Promoting Treatment Initiation Research Regarding Treatmentmentioning
confidence: 99%